2-Butoxytetrahydrofuran and Palmitic Acid from Holothuria scabra Enhance C. elegans Lifespan and Healthspan via DAF-16/FOXO and SKN-1/NRF2 Signaling Pathways - Prapaporn Jattujan; Sirin Srisirirung; Warisra Watcharaporn; Kawita Chumphoochai; Pichnaree Kraokaew; Tanatcha Sanguanphun; Prachayaporn Prasertsuksri; Salinthip Thongdechsri; Prasert Sobhon; Krai Meemon (MDPI AG, 2022)
Extracts from a sea cucumber, Holothuria scabra, have been shown to exhibit various pharmacological properties including anti-oxidation, anti-aging, anti-cancer, and anti-neurodegeneration. Furthermore, certain purified compounds from H. scabra displayed neuroprotective effects against Parkinson's and Alzheimer's diseases. Therefore, in the present study, we further examined the anti-aging activity of purified H. scabra compounds in a Caenorhabditis elegans model. Five compounds were isolated from ethyl acetate and butanol fractions of the body wall of H. scabra and characterized as diterpene glycosides (holothuria A and B), palmitic acid, bis (2-ethylhexyl) phthalate (DEHP), and 2-butoxytetrahydrofuran (2-BTHF). Longevity assays revealed that 2-BTHF and palmitic acid could significantly extend lifespan of wild type C. elegans. Moreover, 2-BTHF and palmitic acid were able to enhance resistance to paraquat-induced oxidative stress and thermal stress. By testing the compounds' effects on longevity pathways, it was shown that 2-BTHF and palmitic acid could not extend lifespans of daf-16, age-1, sir-2.1, jnk-1, and skn-1 mutant worms, indicating that these compounds exerted their actions through these genes in extending the lifespan of C. elegans. These compounds induced DAF-16::GFP nuclear translocation and upregulated the expressions of daf-16, hsp-16.2, sod-3 mRNA and SOD-3::GFP. Moreover, they also elevated protein and mRNA expressions of GST-4, which is a downstream target of the SKN-1 transcription factor. Taken together, the study demonstrated the anti-aging activities of 2-BTHF and palmitic acid from H. scabra were mediated via DAF-16/FOXO insulin/IGF and SKN-1/NRF2 signaling pathways.